2019
DOI: 10.1111/jan.13960
|View full text |Cite
|
Sign up to set email alerts
|

Instruments to assess mental health‐related stigma among health professionals and students in health sciences: A systematic psychometric review

Abstract: Aim:To evaluate the psychometric properties of the instruments to assess the mental health-related stigma among health professionals and students in health sciences.Background: Evidence on the stigmatization by health professionals of people with mental health illness is increasingly compelling. Valid and reliable instruments are needed for the assessment of mental health-related stigma and effectiveness of anti-stigma interventions.Design: Systematic psychometric review. Review methods:We included studies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 51 publications
1
25
0
2
Order By: Relevance
“…Neither the ATP-30 nor the AMI were included in a recent systematic review of the psychometric properties of instruments to assess stigma related to mental illness among professionals and students in the health sciences. 46 That study found the Opening Minds Scale for Health Care Providers (OMS-HC) 47 to be the most widely used instrument across published studies. Importantly, we did not include a metric for self-stigma and help-seeking behaviors and intervening barriers, such as the validated Self-Stigma of Seeking Help (SSOSH) questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Neither the ATP-30 nor the AMI were included in a recent systematic review of the psychometric properties of instruments to assess stigma related to mental illness among professionals and students in the health sciences. 46 That study found the Opening Minds Scale for Health Care Providers (OMS-HC) 47 to be the most widely used instrument across published studies. Importantly, we did not include a metric for self-stigma and help-seeking behaviors and intervening barriers, such as the validated Self-Stigma of Seeking Help (SSOSH) questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“… 24 26 For this study we used the OMS-HC as outcome measure, rather than the similarly well-validated Attitudes to Psychiatry (ATP-30) 27 and Attitudes to Mental Illness (AMI) 28 we had relied on for our previous study. Our rationale was twofold: first, the OMS-HC captures not just attitudes and their degree of stigmatization, but also the key constructs of social distance and disclosure/help-seeking; second, the OMS-HC is broadly used, 17 efficient, and short (15 total items, compared to 30 for the ATP and 20 for the AMI).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of the psychometric properties of instruments to assess mental health-related stigma among health professionals and students in the health sciences found the OMS-HC to be the most widely used instrument across published studies. 17 …”
Section: Methodsmentioning
confidence: 99%
“…Each item of this scale has scores ranging from 1 to 5, and the full 15-item OMS-HC score can range from 15 (least stigmatizing) to 75 (most stigmatizing) [4]. A recent systematic review of all available instruments that assess mental health related stigma among health care professionals concluded there is no “gold standard” tool; however, the 15-item OMS-HC was identified as the strongest available tool supported by evidence [67]. However, another recent multi-center study published online which investigated the validity of this scale, utilizing Rasch modeling, with undergraduate nursing students did not support its use as a global estimate of stigma [68].…”
Section: Methodsmentioning
confidence: 99%